THE WOMEN’S SUFFERING IN THE NOVEL THE HANDMAID’S TALE BY MARGARET ATWOOD - abbas abbas (JURNAL ILMU BUDAYA, 2020)
The research discusses social problems experienced by women in a literary work entitled The Handmaid's by Magaret Atwood Magaret. The social problems in question are discussed the social problem of women that happened in the novel The Handmaid’s Tale and described the impact of social problem on women characters in the novel. The suffering that befell women handmaids such as Offred, Ofglen, Janine, and others occurs in a country called the Republic of Gilead. The research uses the Structuralism Approach, a literary research method that emphasizes structural aspects in the form of character, plot, setting, theme, and others. Gender study in literature becomes the perspective of this research which highlights social injustice towards female characters in the fictional story. The research data are then analyzed by using qualitative research methods and explained descriptively. The results of this study indicate that during the reign of the Gilead Republic, women experienced various social problems in the form of separation from family, not getting proper education, restrictions on freedom, forced childbirth for elite families, and the obligation to perform certain rituals. The social problems experienced by these women resulted in severe depression that almost claimed their lives.